Skin Color May Predict Intra-Abdominal Adhesions During Repeated Caesarean Section Deliveries - Altınboğa, Orhan; Karakoç, Gökhan; Eroğlu, Hasan; Akpınar, Funda; Erol, Seyit Ahmet; Yakıştıran, Betül; Tekin, Özlem Moraloğlu; Yucel, Aykan (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Objective Caesarean rates have increased rapidly for various reasons recently. One of the important reasons among these is medicolegal problems. Our aim with this study was to preoperatively predict abdominal adhesion density by combining the scar tissue morphology formed in the post-caesarean Pfannenstiel incision line and the skin color scoring of the patients.Material and methods Patients who had undergone one caesarean section previously, completed their terms (37−39 weeks) and were under 35 years old were included in the study. Skin color scoring of the patients was performed using the Fitzpatrick skin color scale. Intra-abdominal adhesion scoring of the participant patients was performed using Nair’s adhesion scoring system.Results The change in abdominal adhesion scores was evaluated based on the Fitzpatrick color scale. Adhesion scores per the Nair intra-abdominal adhesion scoring system were found to be 0.04±0.209 in the FP1 group, 0.35±0.662 in the FP2 group, 1.58±0.923 in the FP3 group, and 2.33±0.577 in the FP4 group (p<0.05). These results showed a significant increase in adhesion density with increasing skin color darkness. Based on these results, it was observed that the abdominal adhesion scores and the frequency of depressed skin scar were significantly increased with increasing Fitzpatrick scores (p<0.05).Conclusion The aim of this study was to increase the prediction rates by adding the skin color scoring to the scar tissue characteristics, which have been used in previous studies. The results of this study indicate that the combination of these two parameters may be more effective in predicting intra-abdominal adhesions. Nevertheless, there is a need for studies with a much higher number of patients and multiple parameters to be able to predict intra-abdominal adhesion density preoperatively with greater accuracy.
Keywords: Skin color; adhesion; scar tissue